2011
DOI: 10.1039/c1cp21193e
|View full text |Cite
|
Sign up to set email alerts
|

Protonation/deprotonation effects on the stability of the Trp-cage miniprotein

Abstract: The Trp-cage miniprotein is a 20 amino acid peptide that exhibits many of the properties of globular proteins. In this protein, the hydrophobic core is formed by a buried Trp side chain. The folded state is stabilized by an ion pair between aspartic acid and an arginine side chain. The effect of protonating the aspartic acid on the Trp-cage miniprotein folding/unfolding equilibrium is studied by explicit solvent molecular dynamics simulations of the protein in the charged and protonated Asp9 states. Unbiased R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Traditionally, the modulation of electrostatic interactions in proteins was done by changing the pH or to a lesser degree changing the ionic strength of the solution (8,9). Such approaches are complicated by the difficulties of predicting the titration properties of individual amino acid residues in the context of ensembles of protein conformations that are sampled during the folding reaction (10). A more attractive approach is to modulate electrostatic interactions via substitutions that perturb the thermodynamic and kinetic properties of proteins using simple and computationally tractable model systems.…”
mentioning
confidence: 99%
“…Traditionally, the modulation of electrostatic interactions in proteins was done by changing the pH or to a lesser degree changing the ionic strength of the solution (8,9). Such approaches are complicated by the difficulties of predicting the titration properties of individual amino acid residues in the context of ensembles of protein conformations that are sampled during the folding reaction (10). A more attractive approach is to modulate electrostatic interactions via substitutions that perturb the thermodynamic and kinetic properties of proteins using simple and computationally tractable model systems.…”
mentioning
confidence: 99%
“…Finally, substitutions at surface positions that were predicted not to contribute to the protein stability due to the charge-charge interaction were found to have stability similar to the wild type ubiquitin. The effects of single site substitutions on protein stability were subsequently tested on over 15 different proteins that varied in size, secondary structure content and overall topology [56][57][58][59][60][61][62][63][64][65][66][67]. In all cases it was found that computational modeling can qualitatively predict the effects of substitutions at surface charge positions on the proteins stability.…”
Section: Effect Of Charge-charge Interactions On Protein Stabilitymentioning
confidence: 99%
“…For biological molecules, protonation is a basic process that can have a profound impact on structure by strongly affecting non-covalent intra-and intermolecular interactions. [1][2][3][4][5][6][7] For peptides and proteins, the amine moiety is the most commonly preferred protonation site and protonated amines can engage in various interactions with other functional groups to play key roles in diverse processes such as protein/peptide folding, 2,4 proton transfer dynamics 1, 3 or peptide backbone dissociation. [8][9][10] Recently, these interactions have also been recognized to be of importance in the formation of metastable amino acid clusters [11][12][13][14] with the possible relevance to aggregation related diseases such as phenylketonuria.…”
Section: Introductionmentioning
confidence: 99%